Factors influencing the sexual drive of Russian women of reproductive age in the digital age - Anna I. Fedorova; Anna V. Kazakova; Svetlana M. Chechko; Gennadiy S. Kozupitsa; Irina E. Dufinets (Гинекология, 2023)
Aim. To assess the impact of age, number of sexual partners, having children, family income, and time spent with a smartphone or computer on the sexual drive of women of reproductive age in the era of information technology.